The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4269/ajtmh.12-0587
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of L. (L.) chagasi Excreted-Secreted Antigens (ESAs) for Visceral Leishmaniasis Diagnosis Is Due To Low Levels of Cross-Reactivity

Abstract: Abstract. The analysis of promastigote excreted-secreted antigen (ESA) reactivity with 53 visceral leishmaniasis (VL) cases showed that each sample reacted regardless of the antigen or the Leishmania species used in enzyme-linked immunosorbent assay (ELISA) displayed 100% positivity with the L. (L.) chagasi ESA-blot recognizing bands of molecular weight ranging from 26.5 to 31.5 kDa. The analysis of 160 non-visceral cases showed that 5% of the samples crossreacted with the L. (L.) chagasi ESA-ELISA and 9.4% re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The test was then marketed (LEISHMANIA WB IgG, LDBIO Diagnostics, France), and is currently used as a VL confirmation technique in France (Haute Autorité de Santé, 2017). Other studies in patients with VL due to L. infantum also highlighted the excellent results of this test that targets different antigenic fractions (Tebourski et al, 1994;Marty et al, 1995;Santos-Gomes et al, 2000;Pinedo-Cancino et al, 2013;Seyyedtabaei et al, 2017;Heidari et al, 2019). In the immunocompetent patients included in these studies, sensitivity (90-100%) and specificity (98-100%) were excellent.…”
Section: Western Blotmentioning
confidence: 81%
“…The test was then marketed (LEISHMANIA WB IgG, LDBIO Diagnostics, France), and is currently used as a VL confirmation technique in France (Haute Autorité de Santé, 2017). Other studies in patients with VL due to L. infantum also highlighted the excellent results of this test that targets different antigenic fractions (Tebourski et al, 1994;Marty et al, 1995;Santos-Gomes et al, 2000;Pinedo-Cancino et al, 2013;Seyyedtabaei et al, 2017;Heidari et al, 2019). In the immunocompetent patients included in these studies, sensitivity (90-100%) and specificity (98-100%) were excellent.…”
Section: Western Blotmentioning
confidence: 81%
“…Several studies demonstrate that promastigote antigens of Leishmania cross-react with sera showing positive reactions against antigens of malaria and Chagas disease ( Romero et al, 2009 , Pinedo-Cancino et al, 2013 , Toledo-Machado et al, 2015 ). In this study, sera positive for malaria and Chagas disease showed considerable cross reactivity in the p-ELISA while the rK39 ICT and IFAT did not.…”
Section: Discussionmentioning
confidence: 99%
“…Exoantigens from L. seymouri (TCC011E) and C. fasciculata (TCC039) were obtained as previously described for excreted-secreted antigens (ESA) of L. (L.) infantum chagasi 20 (MHOM/BR/1972/LD). Briefly, exoantigens from L. seymouri and C. fasciculata were recovered from RPMI-1640 medium containing 1-5 x 10 8 cultured parasites/mL after incubation for 24 h at 26 °C without agitation, and stored in small aliquots at -40 °C.…”
Section: Short Communicationmentioning
confidence: 99%
“…and anti- T. cruzi antibodies has been overlooked. In contrast, exoantigens of T. cruzi 15 , and Leishmania spp 16 have been studied, have performed well in the diagnosis of CD 17 , 18 , and have also been promising for the diagnosis of VL 19 - 21 and ATL 20 - 23 .…”
Section: Short Communicationmentioning
confidence: 99%
See 1 more Smart Citation